DUNDRUM-2: Prospective validation of a structured professional judgment instrument assessing priority for admission from the waiting list for a Forensic Mental Health Hospital - Kennedy, Harry; O'Neill, Conor (My University, 2011)
Background: The criteria for deciding who should be admitted first from a waiting list to a forensic secure hospital are not necessarily the same as for assessing need. Criteria were drafted qualitatively and tested in a prospective 'real life' observational study over a 6 month period. Methods: A researcher rated all those presented at the weekly referrals meeting using the DUNDRUM-1 triage security scale and the DUNDRUM-2 triage urgency scale. The key outcome measure was whether or not the individual was admitted. Results: Inter-rater reliability and internal consistency for the DUNDRUM-2 were acceptable. The DUNDRUM-1 triage security score and the DUNDRUM-2 triage urgency score correlated r = 0.663. At the time of admission, after a mean of 23.9 (SD35.9) days on the waiting list, those admitted had higher scores on the DUNDRUM-2 triage urgency scale than those not admitted, with no significant difference between locations (remand or sentenced prisoners, less secure hospitals) at the time of admission. Those admitted also had higher DUNDRUM-1 triage security scores. At baseline the receiver operating characteristic area under the curve for a combined score was the best predictor of admission while at the time of admission the DUNDRUM-2 triage urgency score had the largest AUC (0.912, 95% CI 0.838 to 0.986). Conclusions: The triage urgency items and scale add predictive power to the decision to admit. This is particularly true in maintaining equitability between those referred from different locations.Key words: waiting lists, triage, urgency, forensic psychiatry, secure hospitals, needs assessment.
PUBLISHED
Keywords: Psychiatry; DUNDRUM-2